2014
DOI: 10.5194/hessd-11-5487-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infiltration well to reduce the impact of land use changes on flood peaks: a case study of Way Kuala Garuntang catchment, Bandar Lampung, Indonesia

Abstract: Abstract. Significant land use changes due to rapid development, a central issue in Bandar Lampung and high rainfall intensity are the main triggers for frequent flooding. This study was carried out to define design rainfall intensity based on analysis of hourly temporal rainfall pattern for calculating design discharge, predict the impact of land use changes on flood peaks, and predict the impact of infiltration well on flood peak reduction. The results showed that rainfall distribution pattern for storm dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Reinforcing this result, Caputo (2012) found reductions ranging from 12 to 29%. These results are similar to those presented by Kusumastuti et al (2014), as they have found reductions nearly above 25% when using infiltration wells with 5-year-return period storms.…”
Section: Discussion and Recommendationssupporting
confidence: 90%
See 1 more Smart Citation
“…Reinforcing this result, Caputo (2012) found reductions ranging from 12 to 29%. These results are similar to those presented by Kusumastuti et al (2014), as they have found reductions nearly above 25% when using infiltration wells with 5-year-return period storms.…”
Section: Discussion and Recommendationssupporting
confidence: 90%
“…Some of them are the residential reservoirs, green roofs, permeable pavement, infiltration trenches, and infiltration wells. The use of the latter two were particularly studied by Silva (2007), Caputo (2012), and Kusumastuti et al (2014) in situations comparable with the ones simulated for Palmas.…”
Section: Urbanization and Stormwater Drainagementioning
confidence: 99%
“…Some are mainly concerned with the effects of stormwater (Li et al, 2012;Locatelli et al, 2017). Furthermore, the studies technically make a calculation model related to the capacity of infiltration wells (Jang et al, 2018;Kusumastuti et al, 2014;Li et al, 2011). There is a need for a new evaluation of infiltration wells and preliminary findings regarding a new perspective on groundwater conservation in densely populated areas through direct measurements in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Its population is about 1.5 million. The rapid economic growth is encouraging an urbanization and land use changes 1) , those sometimes increase damages by river floods.…”
mentioning
confidence: 99%